KOMPETISI TANAMAN DALAM BUDIDAYA LORONG - Titiek Islami; Syakur Syakur (BUANA SAINS, 2006)
Alley cropping system has been widely understood as a very effective in soil and water conservation paractices. This system is able to decrease surface run off, and at the same time increase soil fertility and productivity. However, there is also a possibility the occurence of a detrimental effect due to crop competition between the hedgerow crops and the crops. An experiment has been conducted to study the competition between the food crops and the hedgerow crops in alley cropping system. The meassurement was carried out at Jatikerto, in 2002. The hedgerow crops used in this experiment were: (a) without hedgerows, as a control, (b) Gliricidia planted with stem cutting, (c) Gliricidia planted with seed. (c) elephant grass, and (d) Vetiver. The food crops planted in the row was rainy season maize, and followed by dry season maize. The experiment results show that in Gliricidia hedgerow, both planted with seed and stem cutting, there was a light competition and no nitrogen nutrient competition. In elephant grass hedgerow, there was a nitrogen nutrient competition. When there was enough rain, although the crops water used in alley cropping system is higher than that in non alley system, there is no significant competition in crop water used. Crop water competition, especially in Gliricidia and elephant grass hedgerow, occurred during limited water avalibility at dry season